DIVERSITY OF FERNS (PTERIDOPHYTA) IN THE SEVERAL MOUNTAINS OF WEST JAVA - Suryana Suryana; Betty Mayawatie; Joko Kusmoro; Budi Irawan (Universitas Medan Area, 2020)
The diversity of ferns (Pteridophyta) in the five mountainous in West Java (Mt. of Patuha, Papandayan, Tangkuban Perahu, Pangrango, and Guntur) has not been widely reported. The aim of this research was to obtain data on diversity and similarity of fern species in the five mountains in West Java. This research was conducted by exploring and descriptive analysis method. Comparison of species diversity among all reseach field were calculated by the index of species similarity according to Sorenson. The diversity of ferns in Mt. Patuha, Papandayan, Tangkuban Perahu, Pangrango, and Guntur were 27, 14, 26, 40 and 5 species, respectively. The total number of ferns species in five locations are 83 species from 25 families. Comparison of species diversity among fileds based on the Sorenson similarity index is low (<50%), except between the Mt. Patuha and Mt. Papandayan areas is high (> 50%).